Unlocking synergies: how coopetition can generate sustained value in food aid supply chains - Sawyerr, Emmanuel; Bourlakis, Michael (Emerald, 2026)
Purpose: Food insecurity remains a pressing global concern, with the role of charitable surplus food redistributors becoming increasingly crucial. Previous studies have highlighted the need for increased cooperation among redistributors who also compete for both surplus food and funding. Inspired by the benefits of coopetition in commercial food supply chains, this study explores coopetition in the food aid supply chain. Design/methodology/approach: We interviewed managers of 35 purposively sampled surplus food redistributing organisations across England. Our data were analysed abductively, guided by an adapted coopetition conceptual model for the food aid context to derive theoretically and practically meaningful insights. Findings: Redistributors, driven by the shared social concern for disadvantaged groups, commit food and logistics resources both vertically and horizontally to coopetitive relationships. Notwithstanding, power dynamics and value conflicts, along with resource scarcity, undermine joint and firm value creation opportunities and heighten value destruction. Research limitations/implications: By focusing exclusively on the food aid supply chain, this study parsimoniously offers a context-specific theoretical framework whose applicability to other supply chain types may be limited. However, this contextual specificity presents valuable opportunities for future research. Further inquiry could explore the influence of external actors (such as governments and donors), the effects of relational direction across varied supply chain configurations and the governance mechanisms that shape coopetitive dynamics more broadly. Originality/value: Coopetition in the context of surplus food redistribution is underexplored. Our study uniquely engages actors in the two-stage food aid supply chain and proffers pathways for navigating simultaneity and value creation intent towards transformational societal impact.
Keywords: Surplus food redistribution; Coopetition; Simultaneity; Value creation; Food aid supply chain; Cooperation; Competition; 3509 Transportation, Logistics and Supply Chains; 3507 Strategy, Management and Organisational Behaviour; Generic health relevance; 2 Zero Hunger; 35 Commerce, management, tourism and services